Reimagining gender in food systems: A feminist perspective - Ambikapathi, Ramya; Urbani, Ilaria (2025)
Gender dynamics in food systems research are often fragmented and inconsistently integrated across disciplines. This study applies a feminist lens to review 1,221 studies from low- and middle-income countries, assessing the use of five feminist principles. Findings reveal critical gaps, including limited attention to urban food systems, inconsistent gender definitions, and methodological shortcomings. To foster more inclusive research and policy, we propose integrating feminist approaches, strengthening collaborations, and addressing policy gaps with intersectional perspectives. This review highlights the need for a paradigm shift to ensure diverse voices shape food systems research and policy.